Moda : proleće - leto, jesen - zima 1991/1992, proleće - leto 1993 - Pavićević, Borka, 1947- (Beograd : Beogradsi krug, 1994)
Summary in English.
'Texts... published in the weekly magazine Vreme in the period from 1990 to 1993.'
'A document about the chronology of falling apart... a story about collapse, violence, insanity...'
Keywords: Yugoslav War, 1991-1995.